2023
DOI: 10.1111/acel.13817
|View full text |Cite
|
Sign up to set email alerts
|

Effect of peripheral cellular senescence on brain aging and cognitive decline

Abstract: We examine similar and differential effects of two senolytic treatments, ABT‐263 and dasatinib + quercetin (D + Q), in preserving cognition, markers of peripheral senescence, and markers of brain aging thought to underlie cognitive decline. Male F344 rats were treated from 12 to 18 months of age with D + Q, ABT‐263, or vehicle, and were compared to young (6 months). Both senolytic treatments rescued memory, preserved the blood–brain barrier (BBB) integrity, and prevented the age‐related decline in hippocampal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
49
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 133 publications
9
49
1
Order By: Relevance
“…No statistically significant change in body weight from baseline was seen in either group (Figure 9B). In line with previous studies (39,43), we observed significant age-related improvements in forelimb grip strength after ABT-263 treatment (Figure 9C). Moreover, ABT-263 prevented worsening in rotarod performance weeks later (Figure 9D), and markedly improved gait performance from baseline compared to the vehicle control group (Figure 9E-H).…”
Section: The Senolytic Agent Abt-263 Improves Behavioral Performance ...supporting
confidence: 93%
“…No statistically significant change in body weight from baseline was seen in either group (Figure 9B). In line with previous studies (39,43), we observed significant age-related improvements in forelimb grip strength after ABT-263 treatment (Figure 9C). Moreover, ABT-263 prevented worsening in rotarod performance weeks later (Figure 9D), and markedly improved gait performance from baseline compared to the vehicle control group (Figure 9E-H).…”
Section: The Senolytic Agent Abt-263 Improves Behavioral Performance ...supporting
confidence: 93%
“…Furthermore, Dox treatment increased systemic cytokines/chemokines, which were reduced by ABT-263 treatment. Several cytokines/chemokines, which were increased in the current study, have been reported to increase with aging and are associated with impaired cognition of aging(Budamagunta et al, 2023;Scheinert et al, 2015;Serre- Miranda et al, 2020;Speisman et al, 2013;Yegla & Foster, 2019).However, several differences between aging and Dox treatment are likely important when considering Dox treatment as a model of aging. Cognitive deficits may arise due to a variety of cytokines/ chemokines.…”
mentioning
confidence: 59%
“…These cytokines can disrupt the BBB and induce morphological characteristics of activated microglia. Similar to ABT-263 treatment of aging animals(Budamagunta et al, 2023), ABT-263 was effective at preserving the BBB and mitigated morphological changes of microglial soma size, loss of branches, and loss of branch length.…”
mentioning
confidence: 86%
See 2 more Smart Citations